Critical Assessment of the Role of Diet and Nutrition in Mental Health Treatment Plans - Alyami, Ali Abdullah; Al Haider, Hadi Mesfer Hamad; Al Jamhoor, Abdullah Mana Saleh; Al Musharraf, Mansour Ali Hussein; Alyami, Hassan Ali Duhiman; Alhayek , Adel Yayia Saeed; Musallam, Naif Hadi Hussien; Al-Safahan, Mohammed Ahmed Saleh; Alzhoof, Mahdi Abdullah M; Alharbi, Latifa Abdualrahman (Journal of Ecohumanism, 2024)
It has been the focus of research for the last decade as to how nutritional intake interacts with the diet, and lots of faith is being given to dietary intervention in the management of mental health disorders. This paper critically examines the current evidence regarding the relationship between diet nutrition and mental health and discusses how nutritional therapies may be applied. Based on literature analysis and the present data, this paper is aimed at bringing insight into the promising effects of diets to manage some of the symptoms of anxiety, depression, and other psychiatric disorders. Moreover, the paper presents the limitations of the present study and directions for further research in nutritional psychiatry. It ends by arguing that diet and nutrition may or ought to be considered part of the fundamental care for mental health issues and could be useful additions to medication.